Permian-Triassic Pangean basins and foldbelts along the Panthalassan margin of Gondwanaland - Veevers, J. J.; Powell, C. M. (Geological Society of America, 1994)
This volume, a synthesis of the postulated Gondwanan foreland margin, summarizes the current state of knowledge of each of the main sectors of the basin. After reconstructing Permo-Triassic Gondwanaland, separately authored contributions relating to South America, southern Africa, Antarctica and Australia illustrate the relevant geology of each sector using maps and space-time diagrams underpinned by biostratigraphic and radiometric dating. This work provides a stratigraphic and tectonic synthesis which features the specifically Gondwanan glacigene and coal facies, the early and middle Triassic coal gaps, and the interplay of Pangean and Panthalassan tectonics. -A.W.Hall